Mechanisms of Social Influence: A Meta-Analysis of the Effects of Social Information on Female Mate Choice Decisions - Jones, Blake Carlton; DuVal, Emily H. (Frontiers in Ecology and Evolution, 2019)
Social learning about mate choices is taxonomically widespread, and is a potentially important mechanism of social evolution that may affect the strength of sexual selection in a population. We used a meta-analytic approach to estimate the effect of mate-choice copying on reproductive decisions. We evaluated effect sizes across 103 experiments from 40 studies that experimentally measured female mate-choice copying in non-human animals representing Arachnida, Insecta, Malacostraca, Aves, and Actinoperygii. Our goals were to quantify the magnitude of the effect of this form of social influence, and the extent to which it is modified by observer experience, model age relative to the observer, attractiveness of prospective mates, and testing conditions (laboratory vs. free-living). Across all studies, females that observed others choosing a male were on average 2.71 times more likely to mate with that male, or with a phenotypically similar individual, compared to females with no social information (odds ratio 95% credible interval: 1.60-4.80). After corrected for publication bias, this effect remained significant (corrected odds ratio: 1.92, 95% credible interval 1.13-3.40). We found little evidence for phylogenetic effects in the occurrence of mate-choice copying. Indeed, some studies herein found evidence for mate-choice copying in a broad cross-section of species, while others rejected it in their sister taxa. Social information from observed mate choices of others had a considerably stronger effect on mate-choice in free-living subjects than in captive individuals. Inexperienced (virgin) females were more likely to copy mate choices than were experienced females, but the relative age of the model was unrelated to whether copying occurred. Finally, females were more likely to copy the mate choices of others when social information counteracted the observing female’s personal or genetic mating preference. We note the need for increased taxonomic representation in tests of mate-choice copying, given the robust demonstration of effects in taxa studied to date. Such broader information will provide additional insight to the drivers of the differences identified here in tendency to copy mate choices of others.